2011
DOI: 10.1002/jemt.20986
|View full text |Cite
|
Sign up to set email alerts
|

An electron microscopic analysis on the ultra structural abnormalities in sperm of the common carpCyprinus carpio L. inhabiting a polluted lake, Umiam (Meghalaya, India)

Abstract: The present communication reports the ultra structural abnormalities in sperm of a fish species Cyprinus carpio inhabiting a polluted lake, Umiam in North-East India. Transmission electron microscopy (TEM) revealed absence of differentiation between head and midpiece (neck) of some sperm while scanning electron microscopy (SEM) showed some sperm tails with highly reduced length and some sperm with folded tail. Abnormal shape of some sperm head was also revealed by Scanning electron microscopy. Detachment of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
(24 reference statements)
2
7
0
Order By: Relevance
“…Gills of H. fossilis exhibited abnormalities of mitochondria and nuclei in the chloride cells, distortion of mitochondrial membranes, and vacuolization of mitochondria. Membrane distortion of mitochondria in chloride cells was also reported by some authors in the fish Cyprinus carpio exposed to municipal wastes (Massar et al, 2011(Massar et al, , 2012. Mitochondriarich chloride cells are the principal site of trans-epithelial Ca 2+ and Cl − influxes.…”
Section: Transmission Electron Microscopysupporting
confidence: 54%
“…Gills of H. fossilis exhibited abnormalities of mitochondria and nuclei in the chloride cells, distortion of mitochondrial membranes, and vacuolization of mitochondria. Membrane distortion of mitochondria in chloride cells was also reported by some authors in the fish Cyprinus carpio exposed to municipal wastes (Massar et al, 2011(Massar et al, , 2012. Mitochondriarich chloride cells are the principal site of trans-epithelial Ca 2+ and Cl − influxes.…”
Section: Transmission Electron Microscopysupporting
confidence: 54%
“…After sectioning, the sperm slices were stained with sodium acetate and lead citrate. Then we observed the sperm slices under a JEOL JEM-1200EX transmission electron microscope [ 15 , 23 ].…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature on the subject revealed that SEM and EDS have generally been used for studying membrane abnormalities and other surface microstructural defects of erythrocytes associated with specific pollutants in fish and other animals (Rhodes, 1974; Homechaudhuri & Banerjee, 1991; Dey et al, 1999; Luca et al, 2007; Matasin et al, 2011). Use of electron microscopy in assessing fish health status from polluted and environmentally stressed water bodies is extremely low not only for fish blood but also for other tissues (Dey et al, 2009; Domingos et al, 2009; Massar et al, 2011; Rajguru et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…A review of the literature on the subject revealed that SEM and EDS have generally been used for studying membrane abnormalities and other surface microstructural defects of erythrocytes associated with specific pollutants in fish and other animals~Rhodes, 1974; Homechaudhuri & Banerjee, 1991;Dey et al, 1999;Luca et al, 2007;Matasin et al, 2011!. Use of electron microscopy in assessing fish health status from polluted and environmentally stressed water bodies is extremely low not only for fish blood but also for other tissues~Dey et al, Domingos et al, 2009;Massar et al, 2011;Rajguru et al, 2011!. It is logical that studies involving all forms of microscopy and conventional hematological methods may be important in making an in depth analysis of fish blood in relation to the health status of fish in contaminated water bodies. Keeping this in view, light microscopy, SEM, and EDS studies on hematological parameters have been carried out in a fish, C. carpio, inhabiting a large body of water Umiam Lake, in Northeast India!, which is contaminated by city garbage, washing of vehicles, dumping of municipal wastes, and other anthropogenic factors.…”
Section: Introductionmentioning
confidence: 99%